A brief review of recent advances in garnet structured solid electrolyte based lithium metal batteries. (January 2021) - Subramanian, Kannan; Alexander, George V.; Karthik, K.; Patra, Srabani; Indu, M.S.; Sreejith, O.V.; Viswanathan, Raja; Narayanasamy, Janani; Murugan, Ramaswamy
Graphical abstract: Image, graphical abstract Highlights: Lithium metal batteries expected to enhance practical energy density greater than 500 Wh Kg −1 . Integration of lithium metal with current battery technology has posed serious challenges. Replacing the liquid electrolyte by solid electrolytes is considered as one of the strategies. Garnet structured solid electrolytes received considerable attention for developing lithium metal batteries. This review discusses recent advancements on lithium metal batteries based on garnet structured solid electrolytes. These ceramic batteries are attractive option for electric vehicles and grid storage. Ability of these batteries to work at higher temperature makes it viable for tropical conditions. Abstract: The next generation's state of the art for energy storage application is mainly attributed to high capacity lithium metal and electrochemically stable inorganic solid electrolyte based solid state battery. Lithium metal battery technology presently is found to have major problem like dendrite growth and also has interface issues between electrodes and solid electrolyte. Across different inorganic solid electrolytes, garnet structured solid electrolytes have attracted widespread attention because of their high lithium-ion conductivity and stability with potential cathodes and lithium metal. This review focuses on the evolution of garnet structured fast lithium-ion conductors as a solid electrolyte and briefly discusses the problems to be addressed in developing all solid state lithium metal batteries based on lithium garnets.